2008
DOI: 10.1002/ajmg.b.30891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a CREB‐dependent serotonergic pathway and neuronal circuit regulating foraging behavior in Caenorhabditis elegans: A useful model for mental disorders and their treatments?

Abstract: The cAMP-response element binding protein (CREB)-mediated cell signaling pathway is conserved through evolution and participates in a broad range of complex behaviors of divergent species including man. This study describes the integration of genetic, pharmacologic, and anatomic methods to elucidate a serotonergic signaling pathway by which the CREB homolog CRH-1 controls foraging rate (FR) in the model organism C. elegans, along with the complete neuronal circuit through which this pathway operates. In the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…crh-1 also controls the expression of tph-1 , which is required for serotonin synthesis [10], and plays a role in the regulation of aging [11]. We previously showed that CREB was regulated by biogenic amines in C. elegans using the cre::gfp reporter [12], [13], in which a CRE sequence is fused to GFP sequence.…”
Section: Introductionmentioning
confidence: 99%
“…crh-1 also controls the expression of tph-1 , which is required for serotonin synthesis [10], and plays a role in the regulation of aging [11]. We previously showed that CREB was regulated by biogenic amines in C. elegans using the cre::gfp reporter [12], [13], in which a CRE sequence is fused to GFP sequence.…”
Section: Introductionmentioning
confidence: 99%
“…27 A recent study has revealed the important role that CRH-1, the C. elegans homolog of CREB, has on the worm's foraging rate through regulation of tph-1 (tryptophan hydroxylase), which is necessary for serotonin production. 33 Moreover, the same study showed that the serotonergic phenotype of a certain neuron depends on the contribution of this neurotransmitter from an external source provided by a second neuron. 33 This discovery indicates a mechanism of plasticity for the serotonergic circuit in the developing nervous system that might be of utility in understanding certain aspects of neuropsychiatric disorders.…”
Section: Caenorhabditis Elegansmentioning
confidence: 93%
“…33 Moreover, the same study showed that the serotonergic phenotype of a certain neuron depends on the contribution of this neurotransmitter from an external source provided by a second neuron. 33 This discovery indicates a mechanism of plasticity for the serotonergic circuit in the developing nervous system that might be of utility in understanding certain aspects of neuropsychiatric disorders.…”
Section: Caenorhabditis Elegansmentioning
confidence: 93%
“…For example, the use of C. elegans could help to learn more about the mode of action of anesthetics and in the discovery of novel anesthetics [70] . Also, the cAMP-response element binding protein (CREB)-mediated pathway and the complete neuronal circuit which this pathway affects was studied using C. elegans [71] and this model could be used for the study of mental disorders and the discovery of new drugs [72] .…”
Section: C Elegans In Drug Discoverymentioning
confidence: 99%